PENINGKATAN PERTUMBUHAN PENJUALAN UMKM MELALUI PELATIHAN DAN PENDAMPINGAN STRATEGI PEMASARAN DIGITAL BERKELANJUTAN - Sev Rahmiyanti; Wiwiek Rabiatul Adawiyah; Christina Tri Setyorini (Jurnal Abdi Insani, 2026)
The Community Service Activity program aims to improve the understanding and skills of MSME actors in the trade sector in the Boosan area, North Purwokerto District, Banyumas Regency, in utilizing digital marketing strategies precisely, planned, and sustainable to create sustainable sales growth. The program is carried out by the team of the Faculty of Economics and Business, Jenderal Soedirman University through the stages of preparation, need assessment, training, mentoring, and evaluation. Need assessment was carried out through observations, interviews, and Focus Group Discussions which showed that partners did not understand the importance of a planned digital marketing strategy and were still marketing in a limited and undirected manner. Activity methods include counseling, workshops, direct practice of social media and marketplace optimization, as well as continuous mentoring with the support of training modules, activity documentation, and understanding evaluation. The results of Community Service activities show that there is an increase in the understanding and skills of MSMEs in utilizing digital marketing appropriately, planned, and sustainably. Participants stated that after participating in the activity, they learned how to create more engaging content and develop more appropriate promotional strategies to support sustainable sales growth. Evaluation of partner perceptions shows that activities are considered useful and relevant to business needs. Supporting factors for the activity include partner enthusiasm, institutional support, and availability of internet access, while obstacles are time constraints and variations in participants' digital abilities. Overall, this PkM program has succeeded in increasing the digital capacity of MSMEs in accordance with the set goals and has a sustainability plan through follow-up monitoring, periodic mentoring, and module development.